A potential superhard material m-BCN - Rui, S.; Dong, W.; Li-Hua, G. (Сверхтвердые материалы, 2018)
We here propose a new superhard material m-BCN with comparable Vickers hardness to cBN by the use of first-principles calculations. The calculations show that the mentioned m-BCN is a thermodynamically and kinetically stable semiconductor. Hydrostatic calculation shows that it is anisotropic and its incompressibility is very close to c-BN. Structural analysis shows that its excellent mechanical property and thermodynamically stability are inherited from diamond and cBN. These results provide a new clue to find new superhard phase.